Evaluasi Kuat Tekan Batu Bata Tradisional Padang Pariaman Berdasarkan Standar Nasional - Vitri, Gusni; Herman, Hazmal; Zayu, Wiwin Putri; Irawan, Bayu Budi; Mazni, Deni Irda (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
Brick is one of the materials used for construction. One of the brick-producing areas in West Sumatra Province is Padang Pariaman Regency. This study was conducted to determine the quality of bricks, both in terms of shape, strength and forming materials. The tests carried out were shape and size tests, compressive strength tests. The tests were carried out at the Padang Institute of Technology Materials Laboratory by randomly taking brick samples from manufacturing furnaces in 3 (three) Districts in Padang Pariaman Regency. From the test results, recommendations will be made for good quality bricks for construction work and if low quality bricks are found, recommendations will be given for improvements to the brick-making furnaces. The results showed that the size of the test bricks from 3 (three) Districts in Padang Pariaman Regency did not meet the standard size of SNI 15-2094-2000. The average size is 101.34 mm in length, 92.59 mm in width and 49.98 mm in height. The results of the brick compressive strength test were 2.66 N/mm2, which does not meet the SNI 15-2094-2000 standard of at least 5 N/mm2.